Applying The Markowitz Model for Optimal Stock Portfolio Construction to Maximize Investor Returns in The Stock Market - Martia, Dina Yeni; Soebroto, Nina Woelan; Kodir, Moch. Abdul; Pradana, Bagas Putra; Senoaji, Aditya Rizqi (Politeknik Negeri Semarang, 2025)
Increased investor interest in stocks that have sustainability principles (ESG), but price fluctuations that tend to be more stable in the IDX ESG Leaders index often make investors face challenges in obtaining optimal returns. ndex IDX ESG Leaders itself consists of 30 stocks that have good Environmental, Social, and Governance (ESG) assessments, solid financial performance, and high liquidity. The results showed that the resulting optimal portfolio provided an expected return of 0.06% with a risk of 0.68%. This portfolio consists of 9 stocks, namely ASII (17.66%), BMRI (12.85%), BRPT (1.68%), CTRA (7.14%), ICBP (20.77%), POWR (29.39%), PRDA (3.76%), RAJA (3.17%), and SMSM (3.58%).